Marine fuel efficiency for oil and gas offshore operation support activity by application of technology based speed control and contractor performance management - Kelana, Alang; Ligafinza, Audra; Machfud, Machfud; Saipullah, Safri; Soedadi, Suryaningsih (Sustinere: Journal of Environment and Sustainability, 2018)
PHE ONWJ is an upstream oil and gas company performing exploration and production of oil and gas. PHE ONWJ is subsidiary of Pertamina Hulu Energy (PHE) under PERTAMINA Group with working areas of 8.300 km2 covering offshore and onshore sites.  As response to the declining of global oil price, PHE ONWJ is required to reduce its operating costs. One of them is marine operation that accounted for 10% of the total operating cost, 53% of  which is the cost of energy (fuel). The marine fuel efficiency program is a technology based on approach through series of interconnecting activities namely determination of vessels’ economical speed, vessel control by Fuel Monitoring System (FMS) and Vessel Tracking System (VTS), and improvement of contractor performance management. This program has saved diesel fuel consumption for approximately 10,000 kiloliter or equivalent to savings by 34%. Financially it has saved Rp 80 billion and reduce emission by 40 ktons of CO2e during the year 2016. The keys of success of this program are strong commitment to implement economical speed, contractor  partnership, capacity building and awareness to raise contractor’s competence also behaviour towards energy efficiency.